The Effectiveness of STEAM-based Integrated Energy Conversion in Enhancing Critical Thinking Skills and Learning Outcomes - Nurseta, Ratriadi Ari; Woro Sumarni; Barokah Isdaryanti (Universitas Negeri Semarang, 2024)
Critical thinking skill is one of the competences needed by the students. Implementing STEAM-based (Science, Technology, Engineering, Arts and Mathematics) learning in the classroom can trigger their critical thinking to develop as well as their learning outcome. This study aimed to describe the effectiveness of STEAM-based learning system in enhancing 4th grade students’ critical thinking and leaerning outcome in Pati Regency. This quantitative-experimental study was conducted using quasi-experimental with pretest-posttest non-equivalent control group design. Two different schools in Kayen, Pati, were chosen as the subject of the research, and the samples were chosen randomly. There are in total 63 participants, of which 29 of them were chosen from SDN Rogomulyo and 32 students from SDN Pesagi 02. Data collection process was done by using documentation and multiple choices pretest-posttest. N-gain test and independent sample t-test were used for data analyzation. The results of this study showed that STEAM-based energy conversion was proven as effective in enhancing 4th grade students’ critical thinking and their learning outcomes in Pati Regency. This can be seen from the results of the minimum criteria of effectiveness of the learning process after the subject received a treatment which is the implementation of STEAM-based learning.